Protective effects of flavonoids isolated from Agrocybe aegirita on dextran sodium sulfate‐induced colitis. Issue 6 (23rd March 2022) - Zhang, Jianfang; Chen, Xiaomin; Mu, Xinyi; Hu, Mengwei; Wang, Jiang; Huang, Xiaojun; Nie, Shaoping
Abstract : Mushroom derived phytochemical has become the promising agent to treat inflammatory bowel disease (IBD). Here, we investigated the effect of flavonoids from Agrocybe aegirita (AAF) on dextran sodium sulfate‐induced colitis. Our results showed that flavonoids from Agrocybe aegirita had a certain effect on physical signs in mice (improving the weight loss of mice, reducing reducing the DAI index and the spleen index of mice). AAF could also significantly reduce the shortening of the colon, and improve the level of tissue damage and colon inflammation. Besides, AAF could alleviate the colon inflammatory status including reducing the levels of TNF‐α and IL‐1 β and increasing the levels of IL‐10. In addition, AAF significantly promoted the growth of goblet cells and enhance the intestinal barrier function (the secretion of mucin in the colon were increased). In conclusion, flavonoids from Agrocybe aegirita has the potential to relieve the DSS‐induced colitis in mice and could be a novel therapy for combating with IBD.